The effect of using different ramp heights in improving some of the variables Elkinmetekih Im walking for disabled people with unilateral amputation below the knee - Ali, Ashraf (Journal of Physical Education, 2010)
Been in this research study the effect of the use of the slope with different elevations in the improvement of some variables kinematic Special on walking of disabled patients with amputation unilateral below the knee, but the most important research goals is to prepare exercises rehabilitation After wearing the prosthesis by using the slope different heights and see the impact in improving the range motion of joints of the lower limbs during stages of the walk, it has been the application of these exercises on a sample of (8) patients with disabilities who are in the clinic education at the Medical Rehabilitation / Prosthesis & Orthosis Dep. in Institute of Medical Technology-Baghdad. And the main conclusions reached by the researcher that there were significant differences between pretest and post and for the post test improvement in range motion for each of the ankle, knee and hip for a sound limb , knee and hip of the amputation limb. In addition to a significant difference between pre-test and post and for the post test in the number of steps to walk and the time period have. No significant difference found between some stages of the walking foot prosthesis, the most important recommendations is the need to use this exercise rehabilitation in all rehabilitation centres and factories of the Prosthesis & Orthosis .